Stability of space use in Svalbard coastal female polar bears: Intra-individual variability and influence of kinship - Brun, Clément (UiT Norges arktiske universitet, 2020)
Philopatry influences the distribution of animals and can lead to the formation of kinship-based population structures when relatedness among individuals is tightly linked to their proximity. Two different polar bear ecotypes exist in the Barents Sea sub-population: “coastal” bears and “offshore” bears. Coastal bears remain year-round within the Svalbard archipelago whereas offshore bears follow the ice edge. This study assessed the long-term stability of space use in 17 Svalbard coastal female polar bears using satellite telemetry data obtained from 2011 to 2019. Annual and seasonal home range (HR) sizes and locations were analysed in different years in order to assess the intra-individual variability in site fidelity. Additionally, HR sizes and locations of related females belonging to five different matrilines were compared to explore the influence of kinship on site fidelity. The bears showed very stable movement patterns during the study period in both consecutive and non-consecutive years. All annual HRs belonging to the individual bears overlapped; intra-individual annual HR centroids were on average separated by only 15 km (range=2-63 km). Distances separating individual annual HRs were small and were independent of the time gap between two HRs. The number of years separating annual HRs was not correlated to an increase/decrease in overlap. Individual bears exhibited a long-term stability in HR size: the estimated intra-individual variance corresponded to a quarter of the total variance in annual HR size (range=96-22 545 km2). The close proximity of related females showed the presence of a female kin structure year-round. Related females (such as mothers/daughters or sisters) utilized similar areas of the archipelago; their annual HR centroids were on average only separated by 18.4 km (range=2-52 km) which is almost equal to the intra-individual variation. The results of this study are consistent with previous research that investigated site fidelity and kinship structure in polar bears of the Barents ...